Effect of different drying methods on the morphology, crystallinity, swelling ability and tensile properties of nata de coco - Norhayati Pa'e; Nur Idayu Abd Hamid; Nozieana Khairuddin; Khairul Azly Zahan; Kok, Fook Seng; Bazlul Mobin Siddique; Ida Idayu Muhamad (Universiti Kebangsaan Malaysia, 2014)
Nata de coco or bacterial cellulose produced by Acetobacter xylinum is a unique type of biocellulose. It contains more than 90% of water. Dried nata was preferred compared to wet form since it is more convenient and portable with stable properties. Therefore, drying process is necessary in order to produce dried nata de coco. Drying method is a key factor that influenced the properties of dried nata de coco produced. The aim of this study was to investigate the effect of different drying methods on morphology, crystallinity, swelling ability and tensile strength of dried nata de coco. Nata de coco samples were dried using three physical drying methods such as oven, tray dryer or freeze dryer until it achieved 3-5% moisture content. Obviously, the three drying techniques produced web-like structured nata de coco and quite similar crystallinity which was in range between 87 and 89%. Freeze dried sample showed the largest swelling capacity and tensile strength which was found to be 148 MPa. Different drying method gave different properties of nata de coco. Therefore, the present work proposed the most suitable drying method can be utilized based on the properties of end product needed.